Effects of repeated administration of Levosimendan in advanced heart failure in the elderly patient. (14th October 2021) - Fiore, F; Iengo, M; Lepre, D; Fiorentino, M.R; Chiappetti, R; Greco, T; Flocco, V; Cante, T; Puzone, B; Rengo, G; De Vita, A; Piccolo, A; et al.
Abstract: Introduction: Advanced heart failure (AHF) is characterized by repeated episodes of hemodynamic instability, frequent hospitalizations with progressive reduction in quality of life. The aim of the study was to verify in a small group of patients, no longer susceptible to heart transplantation (HT) and left ventricular assistance (LVAD), the effectiveness of monthly treatment with Levosimendan for a period of at least 6 months on quality of life and hospitalization. Materials and methods: 29 elderly patients (≥65 years) with AHF, excluded from the waiting list for HT or no longer eligible for inclusion on the waiting list were enrolled. 12 patients practiced at least 1 infusion of Levosimendan and were considered as cases, while 17 patients with maximized treatment were used as controls. All patients underwent a multidimensional evaluation in which Fraity was assessed according to Fried criteria, cognitive function with Mini-Mental State Examination (MMSE), depressive symptoms with Geriatric Depression Scale (GDS). Results: The 29 patients were followed up monthly and the 12 patients of Levosimendan group practiced an average of 4.6±2.7 infusions in absence of adverse events. The mean age was 73.3±6.2, 87.5% males, with a NYHA class of 3.4±0.4, an ejection fraction of 26.6±4.9 and NT-pro-BNP value of 7016.8±4876.1. Renal function was impaired with eGFR (ml / min) = 36.8±20.1. These patients had been hospitalized 1.8±0.7 times in the previous year. The data are not statistically different compared to the control group although a greater severity of the clinical condition of the case group is evident. The 6 minute walking test (6MWT) was 201.4±118.1 meters. The mean values of Frailty was 4.6±0.5, the GDS 6.4±4.2 and the MMSE 23.8±4.3. Only the MMSE was lower in the case group than in the controls (26.9±1.9, p=0.022). The results in terms of pre-post treatment difference identify an improvement of 35.3±136.3 meters at 6MWT in patients treated with Levosimendan compared to −72.2±94.2 meters in controls (p=0.030), Frailty is reduced by 1.4±1.6 points compared to 0.1±1.1 in controls (p=0.030), the GDS decreases by 0.9±1.5 in cases and increases by 2±2.1 in the control group (p=0.020), the MMSE score increases by 2.12±4.1 in treated patients, while it is reduced by 2.75±2.3 in the control group; p=0.003. The eGFR is reduced in both groups although more in the controls (−1.87±5.8 vs −10.8±11.1; p=0.043). There are no significant differences in mortality while there was less hospitalization during the follow-up period 0.9±0.6 vs 2.4±1.5; p=0.016). Multiple regression analysis shows that hospitalizations reduction is correlated with the recovery of frailty. This association is independent by age and disease severity. Conclusion: Levosimendan improves physical and cognitive function, at the same time a minor decrease in renal function is observed, with a reduction of unscheduled visits to the hospital. Funding Acknowledgement: Type of funding sources: None.